Effect of yeast fermented brown rice flour substitution on nutritional, rheological and textural properties of steamed brown rice bread - Syed Muhammad, Sharifah Kharidah; Ilowefah, Muna; Bakar, Jamilah; Mohd Ghazali, Hasanah (Intech, 2017)
The current study investigated effect of fermented brown rice (Oryza sativa) flour (FBRF) at moderate acidity (pH 5.5) on the nutritional, rheological and textural properties of steamed brown rice bread (SBRB). Brown rice flour was substituted with 40% FBRF and its batter and steamed bread characteristics were evaluated. The results revealed that incorporation of 40% FBRF decreased breakdown, setback and final viscosity of brown rice flour, while its peak viscosity significantly increased. The batter system containing 40% FBRF had softer structure than the control, which was reflected by lower storage module (G′) and loss module (G′′). Furthermore, the crumb texture of its bread was also significantly (p< 0.05) improved, since it had higher chewiness, cohesiveness and spring-iness, as well as higher specific volume than the control. Incorporation of 40% FBRF significantly increased protein, zinc, nicotinic acid and pyridoxine contents of SBRB. However, its content of antioxidant activity, total γ‐oryzanol and phytic acid significantly decreased. This investigation approved that FBRF can be used as a valuable ingredient to modify technological and nutritional properties of steamed brown rice bread